The Effect of Assistance Quiz Team Model with Lectora Inspire Media on Biology Learning Outcomes and Student Activity - Fauziah Nur Hasanah; Aulia Novitasari; Bambang Sri Anggoro (Universitas Veteran Bangun Nusantara Sukoharjo, 2022)
Learning outcomes are indicators of success in learning, learning outcomes are closely related to activity, namely if student learning activities are good then learning outcomes will be good, so that activeness and learning outcomes are important to have, but the reality in school learning outcomes and student activity is low, this is because the model and the media used does not facilitate active students in learning which has an effect on learning outcomes, one solution to the problem of the media and the module is the use of the quiz team model assisted by the lectora inspire. The purpose of this study was to determine the effect of the Quiz Team model with the help of Lectora Inspire on learning outcomes and activeness of class X. The design of this study was a pretest - posttest control group design with a quasi-experimental type. The sampling technique using cluster random sampling was obtained X MIA 1 as the experimental class and X MIA 2 as the control class. Hypothesis testing using MANOVA obtained sig 0.00 < 0.05, meaning that there is an effect of the Quiz Team model assisted by the Lectora Inspire media on learning outcomes and student activity.